X4CP32: a new parallel/reconfigurable general-purpose processor - Soares, R.; Azevedo, A.; Silva, I. S. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
The X4CP32 is a parallel/reconfigurable microprocessor with 2 programming levels. Although it is a general-purpose microprocessor, it has the reliable performance of a reconfigurable architecture. We expose its architecture and programming levels, and discuss the powerful interaction between parallel programming and reconfiguration. It shows two performance-optimized implementations of matrix multiplication using both parallel and reconfigurable paradigms and a parallel implementation of miner intelligent agents.